Pengaruh Kesadaran Wajib Pajak, Pelayanan Pegawai Pajak Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Pada Kantor Pelayanan Pajak Pratama Jakarta Kebon Jeruk Dua Tahun 2016 – 2020 - Dea Danisa; Khairur Raziqiin (Jurnal Ilmu Administrasi Publik, 2021)
The purpose of this study was to determine the effect of taxpayer awareness on taxpayer compliance at the Primary Tax Office of Kebon Jeruk Dua, Jakarta in 2016-2020, the effect of tax employee services on taxpayer compliance at the Primary Tax Office of Kebon Jeruk Dua, Jakarta in 2016- 2020, the effect of tax sanctions on taxpayer compliance at the Primary Tax Office of Kebon Jeruk Dua, Jakarta in 2016-2020, and the effect of taxpayer awareness, tax employee services, and tax sanctions simultaneously on taxpayer compliance at the Primary Tax Office of Kebon Jeruk Two, Jakarta in 2016- 2020.